2012
DOI: 10.1101/cshperspect.a009662
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic Neurotransmitter-Gated Receptors

Abstract: Since the discovery of the major excitatory and inhibitory neurotransmitters and their receptors in the brain, many have deliberated over their likely structures and how these may relate to function. This was initially satisfied by the determination of the first amino acid sequences of the Cys-loop receptors that recognized acetylcholine, serotonin, GABA, and glycine, followed later by similar determinations for the glutamate receptors, comprising non-NMDA and NMDA subtypes. The last decade has seen a rapid ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
100
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(103 citation statements)
references
References 248 publications
(301 reference statements)
3
100
0
Order By: Relevance
“…For instance, we showed that performing the F119Y and M121F mutations on Lily results in an acceleration of the desensitization kinetics (16). Extensive mutagenesis work has shown that the entire interface is involved in fine tuning of the allosteric response to agonist (18,19).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, we showed that performing the F119Y and M121F mutations on Lily results in an acceleration of the desensitization kinetics (16). Extensive mutagenesis work has shown that the entire interface is involved in fine tuning of the allosteric response to agonist (18,19).…”
Section: Resultsmentioning
confidence: 99%
“…Structurally, NMDARs are heteromeric tetramers typically consisting of two obligatory GluN1 subunits and two accessory GluN2 subunits (see Smart and Paoletti 2012). Some subunits also have multiple isoforms and, in some cases, multiple splice variants Sugihara et al 1992).…”
Section: Nmda-type Glutamate Receptorsmentioning
confidence: 99%
“…Among the better understood groups are the membrane proteins, which include the cardinal functional proteins of the excitatory synapsethe glutamate receptors (AMPA, NMDA, and metabotropic glutamate receptors)-as well as other ion channels and adhesion molecules (see Smart and Paoletti 2011;Missler et al 2011).…”
Section: Membrane Proteins Of the Psdmentioning
confidence: 99%